2005
DOI: 10.1093/eurheartj/ehi472
|View full text |Cite
|
Sign up to set email alerts
|

Risk of complications during pregnancy after Senning or Mustard (atrial) repair of complete transposition of the great arteries

Abstract: In this largest report on pregnancy in women with atrial-corrected TGA to date, a high incidence of obstetric complications and mortality in the offspring was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
90
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(102 citation statements)
references
References 24 publications
8
90
3
Order By: Relevance
“…This is lower than in other studies, in which 25-35% deterioration was reported. 3, 14 The lower rate is possibly due to careful and accurate follow-up care in experienced centers, and that patients with unfavorable prognosis were advised against pregnancy early on. Even so, only 33% returned to their prepregnancy state, whereas in other studies up to 70% recovery women after ASO, describing the course of 60 pregnancies in 34 women.…”
Section: Trigas V Et Almentioning
confidence: 99%
“…This is lower than in other studies, in which 25-35% deterioration was reported. 3, 14 The lower rate is possibly due to careful and accurate follow-up care in experienced centers, and that patients with unfavorable prognosis were advised against pregnancy early on. Even so, only 33% returned to their prepregnancy state, whereas in other studies up to 70% recovery women after ASO, describing the course of 60 pregnancies in 34 women.…”
Section: Trigas V Et Almentioning
confidence: 99%
“…Documented cardiac, obstetric and neonatal events were classified according to predefined criteria. 12 …”
Section: Study Protocolmentioning
confidence: 99%
“…Our only atrial switch patient had good systemic RV function, no significant TR and no previous arrhythmias, putting her in a more advantageous position for a good maternal outcome. [6,[21][22][23] Both women with Fontan palliation had good NYHA status, retained ventricular function and no significant atrioventricular valve regurgitation at baseline, all factors considered favourable with this type of circulation. [6] However, a previous history of atrial arrhythmias requiring treatment and a possibly less efficient type of Fontan circuit (classical Fontan with right atrium to pulmonary artery conduit) in the patient with AP Fontan resulted in a difference in occurrence of cardiac events between the pregnancies.…”
Section: Discussionmentioning
confidence: 90%